2019
DOI: 10.1002/glia.23593
|View full text |Cite
|
Sign up to set email alerts
|

Regionally selective knockdown of astroglial glutamate transporters in infralimbic cortex induces a depressive phenotype in mice

Abstract: Elevation of energy metabolism and disturbance of astrocyte number/function in the ventral anterior cingulate cortex (vACC) contributes to the pathophysiology of major depressive disorder (MDD). Functional hyperactivity of vACC may result from reduced astrocytic glutamate uptake and increased neuronal excitation. Here we tested this hypothesis by knocking‐down astrocytic glutamate transporter GLAST/GLT‐1 expression in mouse infralimbic (IL, rodent equivalent of vACC) or prelimbic (PrL) cortices using RNAi stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
47
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 85 publications
(183 reference statements)
7
47
0
3
Order By: Relevance
“…Indeed, a reduced number and volume of astrocytes was found in the prefrontal cortex [ 219 ] and the hippocampus [ 220 ], in the chronic unpredictable stress procedure and chronic social defeat stress paradigm. Interestingly, neurotoxic lesioning of astrocytes in the prefrontal cortex is sufficient to induce depressive-like behaviors in rodents [ 221 ], an effect also found after knocking-down the expression of astrocytic glutamate transporter GLAST/GLT-1 in the prefrontal cortex of the mouse, using small interfering RNA (siRNA) strategies [ 222 ].…”
Section: Nmda Receptors In Depressionmentioning
confidence: 99%
“…Indeed, a reduced number and volume of astrocytes was found in the prefrontal cortex [ 219 ] and the hippocampus [ 220 ], in the chronic unpredictable stress procedure and chronic social defeat stress paradigm. Interestingly, neurotoxic lesioning of astrocytes in the prefrontal cortex is sufficient to induce depressive-like behaviors in rodents [ 221 ], an effect also found after knocking-down the expression of astrocytic glutamate transporter GLAST/GLT-1 in the prefrontal cortex of the mouse, using small interfering RNA (siRNA) strategies [ 222 ].…”
Section: Nmda Receptors In Depressionmentioning
confidence: 99%
“…Acute versus more sustained activation of IL may contribute to the variation in the results, with acute effects tending to be anxiogenic whilst prolonged effects are more likely anxiolytic. However, very recently, sustained activation induced by genetic knockdown of the astrocytic glutamate transporter GLAST/GLT-1 expression, induced a depressive-like phenotype on the tail suspension and forced swim tests [169]. Other contributory factors to the variation in findings may therefore include whether the animal was tested in its subjective ‘night’ or ‘day’, with the former being likely to enhance the level of stress experienced; however, this information is not always provided.…”
Section: Emotional Function and The Subcallosal Zonementioning
confidence: 99%
“…It should be noted however that in the latter [173], cannulas passed through the PL to reach the IL, but infusions were not compared with equivalent manipulations of the PL. Nevertheless, additional support of a pro-depressant effect of IL activation in the reward domain, sustained activation by knockdown of GLAST/GLT-1 expression reduced sucrose consumption, an effect that was not due to PL involvement [169]. Moreover, IL activation using the GABA antagonist bicuculline dampens the intense eating behavior generated by glutamate disruptions in the nucleus accumbens shell [174].…”
Section: Emotional Function and The Subcallosal Zonementioning
confidence: 99%
“…Fullana et al . found that in mice, selective knockdown of astrocyte glutamate uptake results in a depressive-like phenotype due to serotonergic hypoactivity in the infralimbic cortex area [ 8 ]. There are also many astrocyte-related studies in which antidepressants affect various neurotransmitters, i.e ., serotonin, glutamate, energy homeostasis, and the regulation of blood-brain barrier integrity by astrocytes [ 9 ].…”
mentioning
confidence: 99%